Temporal regulation of tumor growth in nocturnal mammals: In vivo studies and chemotherapeutical potential - Wagner, Paula M; Prucca, César G; Velazquez, Fabiola N; Sosa Alderete, Lucas G; Caputto, Beatriz L; Guido, Mario E (The FASEB journal, 2021)
Tumors of the nervous system including glioblastoma multiforme (GBM) are the most frequent and aggressive form of brain tumors; however, little is known about the impact of the circadian timing system on the formation, growth, and treatment of these tumors. We investigated day/night differences in tumor growth after injection of A530 glioma cells isolated from malignant peripheral nerve sheath tumor (MPNSTs) of NPcis (Trp53 ; Nf1 ) mice. Synchronized A530 cell cultures expressing typical glial markers were injected at the beginning of the day or night into the sciatic nerve zone of C57BL/6 mice subject to a 12:12 hours light/dark (LD) cycle or after being released to constant darkness (DD). Tumors generated in animals injected early at night in the LD cycle or in DD showed higher growth rates than in animals injected diurnally. No differences were found when animals were injected at the same time with cultures synchronized 12 hours apart. Similar experiments performed with B16 melanoma cells showed higher tumor growth rates in animals injected at the beginning of the night compared to those injected in the daytime. A higher tumor growth rate than that in controls was observed when mice were injected with knocked-down clock gene Bmal1 cells. Finally, when we compared day/night administration of different doses of the proteasome inhibitor Bortezomib (0.5-1.5 mg/kg) in tumor-bearing animals, we found that low-dose chemotherapy displayed higher efficacy when administered at night. Results suggest the existence of a precise temporal control of tumor growth and of drug efficacy in which the host state and susceptibility are critical.